2020
DOI: 10.1111/jfpp.14377
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of quality uniformity of ohmic and water bath heating treated pork batter with different fat content

Abstract: The effects associated with fat content (0% to 40%) of pork batter and the positions (center and surface) on both ohmic heating (OH) and water bath heating (WB) treated samples, were investigated. The OH achieved a more uniform temperature distribution in pork batter as compared to WB‐ and OH‐treated samples showed lower cooking loss values for all samples tested. Besides, the thiobarbituric acid reactive substances values showed a tendency to increase as fat content increased for both treatments. The lipid ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 47 publications
2
7
0
Order By: Relevance
“…The results showed much less damages in the protein of ohmically cooked samples and less cooking loss compared with the samples cooked in the water bath, suggesting once again the benefit of ohmic heating as an emerging thermal processing technology. These results were confirmed recently by the same research group who noticed a better impact of ohmic heating on cooking loss, protein oxidation, and lipid oxidation of pork batter in comparison with water bath cooking (Tian et al 2020).…”
Section: Evaluation Of Biochemical Propertiessupporting
confidence: 78%
See 2 more Smart Citations
“…The results showed much less damages in the protein of ohmically cooked samples and less cooking loss compared with the samples cooked in the water bath, suggesting once again the benefit of ohmic heating as an emerging thermal processing technology. These results were confirmed recently by the same research group who noticed a better impact of ohmic heating on cooking loss, protein oxidation, and lipid oxidation of pork batter in comparison with water bath cooking (Tian et al 2020).…”
Section: Evaluation Of Biochemical Propertiessupporting
confidence: 78%
“…Similar results were obtained on beef meat, with colour and tenderness properties of ohmically heated meat samples being better than those of water bath-cooked ones (Tian et al 2016). Moreover, a recent study showed that ohmic heating results in more uniform temperature distribution and better microbiological inactivation compared to traditional water bath cooking (Tian et al 2020).…”
Section: Sensory and Microbiological Analysissupporting
confidence: 70%
See 1 more Smart Citation
“…Ohmic heated samples had a more uniform temperature distribution compared to those heated in a traditional water bath, and the overall results suggested that ohmic heating was suitable for meat processing [55] Turkey breast rolls Radio frequency heating Radio frequency heating allowed a reduction of processing time from 150 min (traditional steam processing) to only 40 min. Radio frequency heated samples had lower redness values and lipid oxidation rates compared to the other samples [56] Pork hams Radio frequency heating Radio frequency heating enabled 50% reduction of processing time.…”
Section: Muscle Food Product Thermal Treatments Main Findings Referencementioning
confidence: 97%
“…In addition, this innovative technique is environmentally friendly, efficient in terms of energy conversion, does not require heat transfer surfaces, and can reduce temperature gradients and increase cooking yield [10,24,70]. Although ohmic heating has shown its effectiveness in inhibiting microbial growth in many applications related to muscle foods [55,69,71], several aspects related to the use of this technique for manufacturing safe food need to be investigated [70].…”
Section: Of 38mentioning
confidence: 99%